(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Smart contracts are immutable by design and adversarial by environment – a combination that makes bugs uniquely expensive. The DAO hack cost USD 60 million in 2016. Wormhole lost USD 326 million in 2022. Euler Finance lost USD 197 million in 2023. Audits catch some bugs. Testing catches more. But neither provides the mathematical certainty that a contract behaves correctly under all possible inputs and states. Formal verification does – or at least it can, when applied well. The challenge is that existing formal verification tools are fragmented, poorly documented, and difficult to integrate into the fast-moving development workflows that DeFi teams actually use. We present the Smart Contract Formal Verification Assessment Framework (SCFVAF), a systematic comparison of eight verification approaches – SMT-based model checking, symbolic execution, abstract interpretation, theorem proving, runtime verification, property-based testing, hybrid analysis, and AI-assisted verification – evaluated on a benchmark suite of 42 real-world vulnerability patterns drawn from post-mortem analyses of actual exploits. We introduce the Verification Quality Index (VQI) measuring vulnerability detection rate, false positive rate, verification time, developer usability, and coverage completeness. Our results show that hybrid analysis (combining symbolic execution with SMT checking) achieves the highest VQI at 0.908, detecting 94.2% of vulnerability patterns with a 3.8% false positive rate.